PP12 Cardiometabolic risk profiles in pre-diabetes and diabetes defined by fasting plasma glucose and HbA1c levels in middle-aged adults. (2nd September 2014) - Millar, SR; Perry, IJ; Phillips, CM
Abstract : Background: The American Diabetes Association (ADA) have recommended glycated haemoglobin A1c (HbA1c ) measurement as an alternative to fasting plasma glucose (FPG) for the diagnosis of pre-diabetes and type 2 diabetes. However, evidence suggests discordance between HbA1c and FPG. The aim of this study was to compare the metabolic profiles in subjects with pre-diabetes and type 2 diabetes, using ADA-recommended HbA1c and FPG diagnostic thresholds. In particular, we examined a range of traditional diabetes risk factors, metabolic syndrome (MetS) features, pro-inflammatory cytokines, acute-phase response proteins, coagulation factors and white blood cell counts to determine which test most accurately identified a greater proportion of subjects at increased cardiometabolic risk. Methods: This was a cross-sectional study involving a random sample of 2047 men and women aged 50–69 years. Binary and multinomial logistic regression were used to explore risk feature associations with pre-diabetes [either HbA1c levels 5.7–6.4% (39–46 mmol/mol) or impaired FPG levels 5.6–6.9 mmol/l] and type 2 diabetes [either HbA1c >6.5% ( >48 mmol/mol) or FPG >7.0 mmol/l]. Receiver operating characteristic curve analysis was used to compare the ability of HbA1c to discriminate pre-diabetes or diabetes defined by FPG. Results: A higher percentage of pre-diabetic individuals with diabetes-related phenotypes were identified by FPG compared to HbA1c . Cardiometabolic profiles in diabetic subjects were broadly similar according to diagnosis by either assay. Odds ratios for obesity, elevated blood pressure, high insulin levels, inflammatory biomarkers and MetS were noticeably increased in pre-diabetic participants classified by both tests, with four-fold increased odds (OR: 4.0, 95% CI: 2.8–5.8) of having three or more MetS features compared to subjects diagnosed by either HbA1c (OR: 1.4, 95% CI: 1.2–1.8) or FPG (OR: 3.0, 95% CI: 1.7–5.1) individually. Conclusion: In middle-aged Caucasian-Europeans, HbA1c alone is a poor indicator of diabetes risk compared to FPG. However, combined use of HbA1c and FPG may be of additional benefit for identifying individuals at substantially increased cardiometabolic risk. Earlier identification of high-risk subjects could enable earlier targeted interventions or therapies, thus attenuating development of type 2 diabetes and associated cardiometabolic complications.